Diminished Feedback Evaluation and Knowledge Updating Underlying Age-Related Differences in Choice Behavior During Feedback Learning - de Haan, Tineke; van den Berg, Berry; Woldorff, Marty G.; Aleman, André; Lorist, Monicque M. (Frontiers in Human Neuroscience, 2021)
In our daily lives, we continuously evaluate feedback information, update our knowledge, and adapt our behavior in order to reach desired goals. This ability to learn from feedback information, however, declines with age. Previous research indicated that especially higher level learning processes such as feedback evaluation, integration of feedback information, and updating of knowledge seem to be affected by age, and recent studies showed how the adaption of choice behavior following feedback differed with age. The neural mechanisms underlying this age-related chance in choice behavior during learning however remains unclear. The aim of this study is therefore to investigate the relation between learning related neural processes and choice behavior during feedback learning in two age-groups. Behavioral and fMRI data were collected, while a group of young (age 18-30) and older (age 60-75) adults performed a probabilistic learning task consisting of 10 blocks of 20 trials. On each trial, the participants choose between a house and a face, after which they received visual feedback (loss vs. gain). In each block, either the house or the face image had a higher probability of yielding a reward (62.5% vs. 37.5%). Participants were instructed to maximize their gains. Our results showed that less successful learning in older adults, as indicated by a lower learning rate, coincided with a higher tendency to switch to the other stimulus option, and with a reduced adaptation of this switch choice behavior following positive feedback. At the neural level, activation following positive and negative feedback was found to be less distinctive in the older adults due to a smaller feedback evaluation response to positive feedback in this group. Furthermore, whereas young adults displayed increased levels of knowledge updating prior to adapting choice behavior, we did not find this effect in older adults. Together our results suggest that diminished learning performance with age coincides with diminished evaluation of positive feedback and reduced knowledge updating related to changes in choice behavior, indicating how differences in feedback processing at the trial level might lead to reduced learning performance across trials.